2018
DOI: 10.1111/ina.12465
|View full text |Cite
|
Sign up to set email alerts
|

Airborne spread of expiratory droplet nuclei between the occupants of indoor environments: A review

Abstract: This article reviews past studies of airborne transmission between occupants in indoor environments, focusing on the spread of expiratory droplet nuclei from mouth/nose to mouth/nose for non-specific diseases. Special attention is paid to summarizing what is known about the influential factors, the inappropriate simplifications of the thermofluid boundary conditions of thermal manikins, the challenges facing the available experimental techniques, and the limitations of available evaluation methods. Secondary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
184
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 165 publications
(607 reference statements)
1
184
0
Order By: Relevance
“…It is therefore obvious that the four samples obtained by the INNOVA cannot indicate both the evolution of the exposure index over time and the time‐averaged exposure index during this period of time. The limitation of the slow instrument to measure accurately is more significant at D = 0.35 m than at D = 1.0 m, basically because the flow interaction in the breathing zone is stronger at D = 0.35 m than it is at D = 1.0 m . In general, the comparison made here suggests that fast concentration measurements using the FCM is a more reliable method for investigating dynamic airborne transmission during short‐term events.…”
Section: Results and Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…It is therefore obvious that the four samples obtained by the INNOVA cannot indicate both the evolution of the exposure index over time and the time‐averaged exposure index during this period of time. The limitation of the slow instrument to measure accurately is more significant at D = 0.35 m than at D = 1.0 m, basically because the flow interaction in the breathing zone is stronger at D = 0.35 m than it is at D = 1.0 m . In general, the comparison made here suggests that fast concentration measurements using the FCM is a more reliable method for investigating dynamic airborne transmission during short‐term events.…”
Section: Results and Analysismentioning
confidence: 76%
“…Indirect transmission occurs when the air exhaled by the infected person disperses and mixes with the room air before it reaches the breathing zone and is inhaled by the exposed person. The risk of cross‐infection from direct transmission can be influenced by a number of different parameters, such as air distribution, distance between the persons, positions and orientations of the persons, breathing mode, activity level, and occupant movement, while the risk of cross‐infection from indirect transmission is influenced mainly by the volume of the occupied space and the supply air flow rate . Past studies have examined these parameters and some important findings have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People naturally move their heads when they speak; this plays a direct role in the perception of conversation . Head posture directly determines exhalation flow direction, which is a key factor influencing the risk of cross‐infection . Body sway during conversation may be understood as a cross‐person coordinative structure that embodies the goals of the joint action system .…”
Section: Discussionmentioning
confidence: 99%
“…Head and body movement and orientation reflect personality, psychopathology, cultural background, social class, etc . In infection transmission, together with various breathing modes, different head and body postures and their variation lead to large variations in the risk of cross‐infection between two closely located individuals . Studies have investigated personal exposure based on relative position and posture without reference to realistic close contact data.…”
Section: Discussionmentioning
confidence: 99%